Produção de hidrogênio verde com uso de energia solar fotovoltaica: uma perspectiva para interiorização da economia do H2V no Ceará. Estudo de caso em usina piloto no sertão central cearense - Abreu, Diego Rocha de (2024)
The state of Ceará has significant potential for renewable energy production due to its climatic conditions and geographic location. This potential has attracted substantial investments for the development of a Green Hydrogen (H2V) economy. However, initially, there is a concentration of in vestments in the Fortaleza Metropolitan Region (RMF), leading to unequal development in other regions of the state, which also have potential for H2V production through renewable energies, such as photovoltaic solar power. This study analyzed a photovoltai c system installed in a municipality in the central hinterland of Ceará in 2020, which used Passivated Emitter and Rear Cell (PERC) monocrystalline silicon panels, designed to produce 7,562 kWh/month and 90,744 kWh/year. A documentary survey was conducted on the actions of the Government of Ceará related to the green hydrogen (H2V) economy, analyzing government websites and legislative documents. The annual energy production of the plant was evaluated, collecting the energy generated in 2022 and 2023. Three scenarios were created to analyze energy production, with the optimistic scenario showing the highest generation of 8,121.50 kWh/month. Considering the use of a commercial electrolyzer, an estimated production of 31,673.85 35,734.60 Nm³/month of H 2 was pr ojected for the scenario with the best energy generation. By gathering information on investments in the H2V economy in Ceará, an investment of over R$ 186 billion and the creation of 11,000 jobs were estimated.